A case report: atropine drops induced psychosis after sublingual administration for sialorrhea treatment in stroke patient. - Mohd Azhar, Nur Syuhada; Abu Hassan, Salmah Anim (2021)
Sialorrhea also known as drooling is defined as excessive saliva in the mouth or hypersalivation. The symptom causes discomfort for most stroke patients or other neurological disorders such as Parkinson's disease. Sialorrhea may affect physical, mental, self-esteem and social life because the patient needs to accommodate the excessive salivation in activity of daily living such as eating, talking, resting and sleeping in addition to psychosocial complications such as social stigma among families and friends. Advanced complications might also develop such as aspiration pneumonia. Even worse, the patient might suffocate with the excessive saliva in the throat. In view of sialorrhea affecting quality of life, the symptomatic treatment is very important. One of the drugs that can reduce salivary production is ophthalmic atropine drops; anticholinergic drops synonymously used for dilatation of pupils and treatment of iritis and uveitis. Utilising the side effect of atropine which is dryness of mouth, atropine eye drops are also used for symptomatic treatment of sialorrhea. Nevertheless, there is no consensus and limited research data regarding the use of sublingual atropine to manage sialorrhea. We describe a case of a 61 years old man with atropine-induced psychosis after a single dose of sublingual atropine 1%. We report the atropine outcomes and possible side effects of psychosis in administering ophthalmic atropine via sublingual route in a stroke patient.